2000
DOI: 10.1034/j.1399-302x.2000.150102.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary mucin as related to oral Streptococcus mutans in elderly people

Abstract: MG1 (MUC5b and MUC4) and MG2 (MUC7), predominant mucins in human whole saliva, provide lubrication and antimicrobial protection for oral tissues. This study examines potential relationships between Streptococcus mutans titers in the oral cavity and the following: mucin concentrations; unstimulated and stimulated whole saliva flow rates; decayed, missing, and filled tooth surfaces; and age of 24 elderly patients. S. mutans titers were determined using Denticult SM. Mucin concentrations were determined using Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 27 publications
0
37
0
1
Order By: Relevance
“…These aberrations are potential diagnostic and/or prognostic markers that could be used in a variety of nanotechnology-based formats being devised by another NIDCR-funded initiative (reviewed by Wong). 66 With regard to oral diseases, IL-1 polymorphisms appear to track with periodontal disease; 83,84 MUC7 levels in elderly patients predict Streptococcus mutans titers, 85 and proteolytic processing of parotid salivary proteins diverges among individuals with different caries experiences. 86 Sjögren's syndrome, which leads to hyposalivation, is associated with a rise in the concentration of several major salivary proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These aberrations are potential diagnostic and/or prognostic markers that could be used in a variety of nanotechnology-based formats being devised by another NIDCR-funded initiative (reviewed by Wong). 66 With regard to oral diseases, IL-1 polymorphisms appear to track with periodontal disease; 83,84 MUC7 levels in elderly patients predict Streptococcus mutans titers, 85 and proteolytic processing of parotid salivary proteins diverges among individuals with different caries experiences. 86 Sjögren's syndrome, which leads to hyposalivation, is associated with a rise in the concentration of several major salivary proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of detection of MUC7 in tears, reported by Jumblatt et al (2003) is therefore likely to be due to its low concentration. Both MUC7 and MUC5B have been shown to participate in bacterial adhesion (Baughan et al 2000;Liu et al 2000a;Situ and Bobek 2000;Thomsson et al 2002).…”
Section: Muc7mentioning
confidence: 99%
“…Our data demonstrate that MUC5B is produced by acinar cells of the healthy lacrimal gland and staining intensity is strongly increased in lacrimal glands of elderly women who were treated with artificial tears. MUC5B has been shown to participate in bacterial adhesion (Baughan et al 2000). Secretion by the lacrimal gland might be a necessary event in ocular surface protection because of its very limited synthesis by the ocular surface epithelia.…”
Section: Muc5bmentioning
confidence: 99%
“…[50][51][52] In 2009, Gursoy and others 53 compared the concentration of a select subset of salivary proteins (elastase, lactate dehydrogenase, IL-1"b, interleukin-6 [IL-6], and tumor necrosis factor-a) and the presence of five pathogens (Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia, and Treponema denticola) in patients with advanced periodontal disease and healthy controls. This study reported an association of salivary IL-1"b and multiple oral pathogens with periodontitis.…”
Section: Oral Disease Detectionmentioning
confidence: 99%